2019
DOI: 10.3390/jmse7110407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Marine Toxin Domoic Acid on Innate Immune Responses in Bay Scallop Argopecten irradians

Abstract: Domoic acid (DA) is an amnesic shellfish poisoning toxin produced by some species of the genera Pseudo-nitzschia and Nitzschia. This toxin has harmful effects on various species, especially scallops. This study aimed to investigate the effects of DA exposure on the immune and physical responses of bay scallop, Argopecten irradians. Various immunological and physical parameters were assessed (acid phosphatase (ACP), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), lipid peroxide (LPO), nitric oxide (NO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The immune system of marine bivalves is sensitive to algal toxins. Chi et al found that exposure to domoic acid impaired immune functions in the bay scallop [ 27 ]. Abi-Khalil et al reported that exposure to PST-producing dinoflagellates significantly increased the susceptibility of oysters to pathogenic vibrio [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The immune system of marine bivalves is sensitive to algal toxins. Chi et al found that exposure to domoic acid impaired immune functions in the bay scallop [ 27 ]. Abi-Khalil et al reported that exposure to PST-producing dinoflagellates significantly increased the susceptibility of oysters to pathogenic vibrio [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several harmful algae can provoke a stimulation of immune functions, while others cause inhibition [ 68 ]. Chi et al [ 27 ] found that exposure to domoic acid impaired immune functions in the bay scallop A. irradians . In P. maximus , the immune system process was one of the enriched terms in the proteins coded by DEGs that showed interaction in STRING ( Figure 2 and Figure 3 , Supplementary Files S6–S8 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is an expansion of Hsp70 (heat shock protein 70 kDa) genes from the Hspa12 subfamily in Mizuhopecten yessoensis [ 71 ], and a gene of this subfamily ( heat shock 70 kDa protein 12A-like ) was up-regulated in P. maximus ( Supplementary File S1 ). A up-regulation of HSP genes after exposure to harmful algae toxins (including domoic acid) has been found in several bivalves [ 27 , 28 , 71 , 72 , 73 , 74 , 75 ], although in A. opercularis , after exposure to domoic acid-producing Pseudo-nitzschia , HSP genes were both up- and down-regulated [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The published data indicate that M. galloprovincialis displays adaptive traits to maintain immune capacity upon prolonged PSTs exposure, including a selective evolutionary advantage [43] and the enhancement of detoxification and antioxidant defense systems [44]. In contrast, the immune system of A. irradians displayed negative effects when faced with the same stress [45], as immuno-depleted, chronic [46], and uncontrolled inflammation caused persistent tissue damage [47]. In summary, accumulative metabolism and mortality reflect differences in external physiological characteristics, and M. galloprovincialis present stronger immune responses to PSTs exposure.…”
Section: Differences In Physiological Characteristics Between M Gallo...mentioning
confidence: 99%